Sources of hepatic glucose production by 2H2O ingestion and Bayesian analysis of 2H glucuronide enrichment. - Delgado, TC (2008)
The contribution of gluconeogenesis to hepatic glucose production (GP) was quantified after (2)H(2)O ingestion by Bayesian analysis of the position 2 and 5 (2)H-NMR signals (H2 and H5) of monoacetone glucose (MAG) derived from urinary acetaminophen glucuronide. Six controls and 10 kidney transplant (KTx) patients with cyclosporine A (CsA) immunosuppressant therapy were studied. Seven KTx patients were lean and euglycemic (BMI = 24.3 +/- 1.0 kg/m(2); fasting glucose = 4.7 +/- 0.1 mM) while three were obese and hyperglycemic (BMI = 30.5 +/- 0.7 kg/m(2); fasting glucose = 7.1 +/- 0.5 mM). For the 16 spectra analyzed, the mean coefficient of variation for the gluconeogenesis contribution was 10% +/- 5%. This uncertainty was associated with a mean signal-to-noise ratio (SNR) of 79:1 and 45:1 for the MAG H2 and H5 signals, respectively. For control subjects, gluconeogenesis contributed 54% +/- 7% of GP as determined by the mean and standard deviation (SD) of individual Bayesian analyses. For the lean/normoglycemic KTx subjects, the gluconeogenic contribution to GP was 62% +/- 7% (P = 0.06 vs. controls), while hyperglycemic/obese KTx patients had a gluconeogenic contribution of 68% +/- 3% (P < 0.005 vs. controls). These data suggest that in KTx patients, an increased gluconeogenic contribution to GP is strongly associated with obesity and hyperglycemia